Scaffolding LSD1 Inhibitors Impair NK Cell Metabolism and Cytotoxic Function Through Depletion of Glutathione - Bailey, Cavan P.; Figueroa, Mary; Gangadharan, Achintyan; Lee, Dean A.; Chandra, Joya (Frontiers in Immunology, 2020)
Cell therapies such as chimeric-antigen receptor (CAR) T-cells and NK cells are cutting-edge methods for treating cancer and other diseases. There is high interest in optimizing drug treatment regimens to best work together with emerging cell therapies, such as targeting epigenetic enzymes to stimulate recognition of tumor cells by immune cells. Herein we uncover new mechanisms of the histone demethylase LSD1, and various inhibitors targeting unique domains of LSD1, in the function of NK cells grown for cell therapy. Catalytic inhibitors (tranylcypromine and the structural derivatives GSK LSD1 and RN-1) can irreversibly block the demethylase activity of LSD1, while scaffolding inhibitors (SP-2509 and clinical successor SP-2577, also known as seclidemstat) disrupt epigenetic complexes that include LSD1. Relevant combinations of LSD1 inhibitors with cell therapy infusions and immune checkpoint blockade have shown efficacy in pre-clinical solid tumor models, reinforcing a need to understand how these drugs would impact T- and NK cells. We find that scaffolding LSD1 inhibitors potently reduce oxidative phosphorylation and glycolysis of NK cells, and higher doses induce mitochondrial reactive oxygen species and depletion of the antioxidant glutathione. These effects are unique to scaffolding inhibitors compared to catalytic, to NK cells compared to T-cells, and importantly, can fully ablate the lytic capacity of NK cells. Supplementation with biologically achievable levels of glutathione rescues NK cell cytolytic function but not NK cell metabolism. Our results suggest glutathione supplementation may reverse NK cell activity suppression in patients treated with seclidemstat.